[OP.7D.03] RENAL DENERVATION IN HYPERTENSIVE PATIENTS NOT ON BLOOD PRESSURE LOWERING DRUGS. (September 2016) - Sanders, M.; de Jager, R.; Bots, M.; Lobo, M.; Blankestijn, P.
Abstract : Objective: Studies on the blood pressure lowering effect of renal denervation (RDN) in resistant hypertensive patients have produced conflicting results. Change in medication usage during the studies may be responsible for this inconsistency. To eliminate the effect of medication usage on blood pressure we focused on unmedicated hypertensive patients who underwent RDN. Design and method: Our study reports on a cohort of patients who were not on blood pressure lowering drugs at baseline and during follow-up from eight tertiary centers. Data of patients were used when they were treated with RDN and had a baseline office systolic blood pressure (SBP) of at least 140 mmHg and/or 24-hour ambulatory SBP of at least 130 mmHg. Our primary outcome was defined as change in office and 24-hour SBP at 12 months after RDN, compared to baseline. Results: Fifty-three patients were included. There were three different reasons for not using blood pressure lowering drugs: 1) documented intolerance or allergic reaction (57%); 2) temporary cessation of medication for study purposes (28%); and 3) reluctance to take antihypertensive drugs (15%). Mean change in 24-hour SBP was −5.7 mmHg (95% confidence interval [CI] −11.0 to −0.4; P = 0.04). Mean change in office SBP was −13.1 mmHg (95% CI −20.4 to −5.7; P = 0.001). Figure 1 represents individual changes in blood pressure after RDN. No changes were observed in other variables, such as eGFR, body–mass-index and urinary sodium excretion. Conclusions: This explorative study in hypertensive patients, who were not on blood pressure lowering medication, suggests that at least in some patients RDN lowers blood pressure. Figure. No caption available.